PoP-ARE: A Tool for Extracting Systems-of-Systems Non-Functional Requirements from Processes-of-Business Processes - Costa, Murilo Gustavo N.; Molina, Sidny de Almeida; Paiva, Débora Maria Barroso; Cagnin, Maria Istela (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2024)
Context: Assuring the interoperability between distinct software systems, which form Systems-of-Systems (SoS), aiming to reach business objectives of alliances of organizations (i.e., fusion, acquisition or partnership) is challenging. One reason is the managerial and operational independence of these systems. Information obtained from the business level of alliances can help SoS requirements engineers to better understand the interoperability and fault tolerance requirements throughout the interoperability to achieve the SoS stability. Objective: We present PoP-ARE, a guideline-based tool for extracting and specifying SoS interoperability and fault tolerance requirements from models of complex and dynamic business processes of alliances of organizations called Processes-of-Business Processes (PoP). Method: To observe the ease of use and usefulness of PoP-ARE, we conducted a study with four SoS engineers of two SoS using the Technology Acceptance Model (TAM). Results: The results indicate that all of the participants agreed with the ease of tool use, and 75% stated its usefulness. Also, they intend to use PoP-ARE in SoS evolution. Conclusion: As PoP-ARE supports the extraction and specification of SoS interoperability and fault tolerance requirements aligned to the business, its outcomes can positively contribute to the SoS stability and the achievement of the business objectives of alliances of organizations.